Krajobraz a nowoczesność. Teoria krajobrazu Karataniego Kōjina - Szeszuła, Szymon (Przestrzenie Teorii, 2025)
The aim of this article is to present the concept of the discovery of landscape as formulated by Karatani Kōjin in his seminal work Origins of Modern Japanese Literature. Karatani’s theoretical proposal remains an important contribution to the debate on the historicity of the basic concepts used to describe the world. He points to the direct connection between modern subjectivity and the relationship to the outside world, arguing that the breakthrough in the epistemological constellation in Japan took place in the third decade of the Meiji era. I present his views against the background of the earlier observations of Shiga Shigetaka and Watsuji Tetsurō.